2010
DOI: 10.1590/s0103-50532010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective hydrogenation of ethyl pyruvate and 1-phenyl-1,2-propanedione on catalysts prepared by impregnation of colloidal platinum on SiO2

Abstract: A hidrogenação enantiosseletiva de piruvato de etila e de 1-fenil-1,2-propanodiona foi estudada a 298 K e sob 40 bar de H 2 sobre um catalisador de platina coloidal estabilizado com cinchonidina (CD) e suportado em sílica. O catalisador foi preparado por impregnação da platina coloidal em sílica, atingindo 1% em massa do metal no suporte. O colóide foi preparado a partir de uma solução aquosa de H 2 PtCl 6 estabilizada com diferentes quantidades de CD. O catalisador foi caracterizado por isotermas de adsorção-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Table 4 shows the conversion levels of different substrates studied at 420 min of reaction and ee obtained using 1.0Rh-3L catalyst. It should be mentioned that even though the enantioselectivity levels remains approximately constant with the conversion in the different studied reactions, conversion levels and pseudo constant rate are higher in lineal diketones, however, are lower in enantioselectivity, in line with results already reported [33][34] . On the other hand, aromatic ketones, PPD and AP, show higher %ee and lower activity, attributed to the structure of the aromatic compounds.…”
Section: Enantioselective Hydrogenationssupporting
confidence: 88%
See 1 more Smart Citation
“…Table 4 shows the conversion levels of different substrates studied at 420 min of reaction and ee obtained using 1.0Rh-3L catalyst. It should be mentioned that even though the enantioselectivity levels remains approximately constant with the conversion in the different studied reactions, conversion levels and pseudo constant rate are higher in lineal diketones, however, are lower in enantioselectivity, in line with results already reported [33][34] . On the other hand, aromatic ketones, PPD and AP, show higher %ee and lower activity, attributed to the structure of the aromatic compounds.…”
Section: Enantioselective Hydrogenationssupporting
confidence: 88%
“…Catalysts with different ligand concentration and metal loading have been used as catalysts in enantioselective hydrogenation reactions of AP, PPD, HD, BD and EP as test reaction. These substrates are interesting due to the applications that have some of its (R)-product of hydrogenation [33][34][35] in synthesis of chiral drugs. Thus, (R)-1-hydroxy-1-phenylpropan-2-one, product of PPD hydrogenation, is a precursor for the production of ephedrine and analogues used as a nasal and bronchial decongestant among others 36 .…”
Section: Introductionmentioning
confidence: 99%
“…First order reaction rate constants, in the hydrogenation of 1-phenyl-1, 2-propanodione at 298 K on Pt/ZrO 2 catalysts. k 1g , 10 3 min -1 k 1R , 10 3 min -1 k 1R , 10 3 min -1 k 2R , 10 3 min -1 k 2S , 10 3 min - Considering the previous results obtained in the ethyl pyruvate hydrogenation and also in the 1-phenyl-1, 2-propanodione hydrogenation [7][8][9][10][13][14][15][16][17][18] , it would be possible to enhance the yield to the desired products by adjusting CD coverage. For that reason the effect of the CD concentration added at the beginning of the reaction has been studied.…”
Section: Catalytic Activity In 1-phenyl-12-propanedione Hydrogenationmentioning
confidence: 99%
“…Heterogeneous enantioselective hydrogenation of diketones on cinchona alkaloid modified platinum represents a promising route for the synthesis of chiral molecules with high optical purity [1][2][3]. As catalysts Pt, Pd and Ir supported on SiO 2 , Al 2 O 3 among others are used [4][5][6][7][8]. Since Orito et al reported the enantioselective hydrogenation of ethyl pyruvate to (R)-ethyl lactate over cinchonidine-modified Pt catalysts with ee's up to 95%, many other research teams have evaluated their catalytic systems in the mentioned reaction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A few research groups have focused their studies in using chiral nanoparticles as catalysts. NPs have been also used as catalysts in reactions such as hydroformylation, allylic alkylation, hydrosilylations, Suzuki and Heck-type, couplings, among others achieving good results [19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%